Assessing and Improving the Knowledge of Sexually Transmitted Infections among High School Adolescents - Itisha S. Jefferson; S. Kayo Robinson; Eleanor Tung-Hahn; Roan Schumann; Synthia Marrero-Conti; Jasmine M. Walton; Eileen Golden; Emily Poon; Murad Alam; Rebecca Tung (Dermatology Research and Practice)
Background. According to the Center for Disease Control and Prevention (CDC), half of the 20 million new sexually transmitted infections (STIs) occur annually in youth aged 15 to 24. It is critical for dermatologists to be able to provide young patients with accessible education about how to identify, prevent, and treat these conditions. Our pilot study sought to assess the impact of a live presentation about STIs in high school students and to evaluate students’ baseline and acquired knowledge about common STIs using a before and after survey. Methods. This survey study was conducted as part of the health education curriculum at a suburban high school. An interactive scenario-based presentation about STIs was given to participants. Identical, deidentified preintervention and postintervention surveys were completed by subjects to assess their baseline and acquired knowledge of STIs. Each question was worth 1 point, for a total of 8 points. Results. 74 high school students were surveyed. Overall, there was a mean improvement of 1.85 points in the posttest score in comparison to pretest score with a standard deviation of 1.58 (p<0.0001). Among all participants, the mean pretest score was 1.07 (SD = 0.75) and the mean posttest score was 2.92 (SD = 1.59). Conclusions. This study demonstrated that many young adults are unaware of the common types of STIs, symptoms, and potential complications. While our scenario-based presentation was effective at providing understandable content to help improve students’ knowledge regarding STIs, additional educational resources in varied formats could likely further these gains.